Human - wildlife conflicts in the southern yungas : what role do raptors play for local settlers? - Salom, Amira (2021)
Fil: Salom, Amira. Centro Austral de Investigaciones Científicas (CADIC-CONICET). Laboratorio de Ecología y Conservación de Vida Silvestre. Ushuaia, Argentina.